2023
DOI: 10.3390/molecules28062464
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Tensile Properties, Biostability, and Biocompatibility of Siloxane–Cross-Linked Polyurethane Containing Ordered Hard Segments for Durable Implant Application

Abstract: This work developed a series of siloxane-modified polyurethane (PU–Si) containing ordered hard segments by a facile method. The polyaddition between poly(ε-caprolactone) and excess diurethane diisocyanate was carried out to synthesize a polyurethane prepolymer with terminal isocyanate groups, which was then end-capped by 3-aminopropyl triethoxysilane to produce alkoxysilane-terminated polyurethane; the target products of PU–Si were obtained with hydrolysis and the condensation of alkoxysilane groups. The chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The data demonstrate that there is no significant difference between samples and all three surfaces did not allow platelets to adhere (A) (<0.5% adhesion vs. TCP). The results were due to the hydrophobicity of TPU, already reported by Villani et al [34], and our findings are in accordance with the literature [44,45]. Quantitative data are supported Figure 6.…”
Section: Evaluation Of Tpu Surface Effect On Platelets Fibrinogen And...supporting
confidence: 93%
See 2 more Smart Citations
“…The data demonstrate that there is no significant difference between samples and all three surfaces did not allow platelets to adhere (A) (<0.5% adhesion vs. TCP). The results were due to the hydrophobicity of TPU, already reported by Villani et al [34], and our findings are in accordance with the literature [44,45]. Quantitative data are supported Figure 6.…”
Section: Evaluation Of Tpu Surface Effect On Platelets Fibrinogen And...supporting
confidence: 93%
“…Furthermore, the capacity of fibrinogen to adhere on modified TPU surfaces was evaluated, since the importance for platelets adhesion. The results, shown in Figure 7 and Table 1, confirmed that a low percentage, with respect to the TCP control, could bind to the surface [44]. There is no significant difference between film and brush, whose surfaces displayed circa 15% of fibrinogen adhesion.…”
Section: Evaluation Of Tpu Surface Effect On Platelets Fibrinogen And...supporting
confidence: 51%
See 1 more Smart Citation
“…It finds applications in industries like textiles, paints, and plastics, where improved surface properties are desired. The same applies in the biomedical and pharmaceutical fields, as the surface of biomaterials, such as implants or drug delivery systems, are used to improve biocompatibility, reduce immunogenicity, and enhance the interaction with biological tissues (see, e.g., [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]).…”
Section: Introductionmentioning
confidence: 99%